ETHNOGRAPHIC STUDIES IN DAGESTAN IN THE PERIOD OF THE GREAT PATRIOTIC WAR - Lysenko, U M (History, Archeology and Ethnography of the Caucasus, 2015)
The article deals with the history of ethnographic studies of Dagestan people during the Great Patriotic War. The author defines the value of the monographic study “The Kubachins and their culture. Historical sketches” by E.M. Schilling and presents the contribution and the most significant achievements of the ethnographers in the study of material and spiritual culture of the nations of Dagestan in the affected period. The author analyzes the activity of ethnographic expeditions organized by the Institute of Ethnography of the Academy of Sciences of the USSR and the Faculty of History of Moscow State University under E.M. Schilling’s command in 1945 and 1946. It is noted that the members of the expedition record ed the data on family life, marriage, maternity and funeral rites, child-rearing, women condition, rules of conduct, blood feud, the rites of hospitality of Dagestan people, described the archaic type of single-chamber house, collected material on domestic crafts.